IMPROVING LITERACY AND UNDERSTANDING OF SHARIAH ECONOMICS FOR INDONESIAN MIGRANT WORKERS IN PENANG - Khulsum, Umi; Utami, Pertiwi; Zuhriyah, Nur Azizah; Basrowi, Basrowi; Yunos, Melinda Siti Asmah Binti (International Journal of Engagement and Empowerment (IJE2), 2024)
Partners in implementing this international community service activity are Indonesian migrant workers from Penang Island and the Consulate General of the Republic of Indonesia (Consulate General of the Republic of Indonesia) Penang. The primary challenge confronting the partners is the low literacy and comprehension of sharia economic and financial practices and the utilization of digital technology in everyday life. This program was conducted at Wisma Indonesia, George Town, Penang, Malaysia. A total of 50 Indonesian migrant workers participated in the enrichment activities performed by the community service team in June 2024. The objective of the enrichment program, which is performed over a single day, is to facilitate comprehension of the tenets and practices of Islamic economics and finance among the partners. The program covers a range of topics, including but not limited to the principles of buying and selling, the operational aspects of Sharia banking, the managerial techniques associated with Sharia marketing, the intricacies of ZISWAF, the ethical considerations inherent to Islamic business practices, the fundamental principles of sharia investment, and the potential applications of digital technologies within the context of the sharia economy. It is evident that there is a pressing need for Indonesian migrant workers, the majority of whom are Muslim, to enhance their literacy and comprehension abilities. It is particularly crucial given that the topics have been selected according to their needs before the speakers arrive to provide the material. Following implementing the focus group discussion method, most migrant workers expressed satisfaction and appreciation for the activity, citing its effectiveness in facilitating their comprehension of authentic Sharia economic and financial practices. Additionally, using digital technology based on Sharia principles was identified as a valuable learning opportunity for migrant workers, enabling them to develop their careers while working in Malaysia. Implementing initiatives aimed at enhancing literacy and comprehension capacity represents an effort by Islamic universities to contribute to enhancing the competencies of Indonesian migrant workers in Malaysia. It is hoped that this can be implemented on a sustainable basis